Effect of utilizing different permeable material in air-to-air fixed plate energy recovery heat exchangeron energy saving - Nasif, M.S. (Asian Research Publishing Network, 2015)
The performance of air-to-air fixed plate energy recovery heat exchanger utilizing porous paper and Mylar film as the heat and moisture transfer media used in ventilation energy recovery systems is presented. This performance is represented by the heat exchanger sensible and latent effectiveness. A simplified air conditioning system which is represented by cooling coil that incorporates air-to-air fixed plate heat exchanger to cool office space is developed. Energy analysis for tropical climate shows that utilizing paper surface heat exchanger in a standard air conditioning system will lead to 78 energy saving as compared with utilizing Mylar plastic film which recovers only sensible heat. Â© 2006-2015 Asian Research Publishing Network (ARPN).